Stationauxiliary operation technology for sonar digital image processing based on machine vision - DAI Zhonghua, JIN Qiaoyuan, YANG Ding, CHENG Yu (Zhihui kongzhi yu fangzhen)
Passive sonar operator of a ship needs to concentrate on observing sonar interface and underwater or surface target situation for a long time to extract key information manually maritime operations when surface vessels pass through sensitive waters, there is the risk of missing and false alarm. A station auxiliary operation technology for sonar digital image processing based on machine vision is proposed. First, the transient signal detection algorithm is used to extract the threat target mutation signal. Secondly, we use trajectory detection algorithm to extract key features of target, such as wideband trajectory and narrowband trajectory. Then, the threat judgment of an incoming threat target in each position within the effective observation range of sonar is generated by synthetically using the situation of a surface or underwater target. Finally, the sonar is automatically controlled to track the threat target according to the result of arbitrage. This technology can effectively reduce the work intensity of sonar operation, shorten the risk of false alarm and improve the threat target adversarial efficiency.